Thinking Differently about ‘False Allegations’ in Cases of Rape: The Search for Truth - Wheatcroft, Jacqueline M.; Walklate, Sandra (International Journal of Criminology and Sociology, 2014)
The myth ‘cry wolf’ continues to pose particular problems for campaigners, policy makers and practitioners. This paper subjects this myth, and the way in which it has been debated, to critical scrutiny with a view to suggesting an alternative and better way of challenging the presumption both in theory and in practice that women ‘cry wolf’. In reflecting on lessons learned that presume believability in establishing rapport from the treatment of children in sexual offence cases the paper suggests that such practices can maximise efficacy in the treatment of women in cases of rape. It concludes that by leaving accusatory language behind, complainants, practitioners and judicial parties may experience more successful pathways to truth.